The Influence of Carbon Emission Disclosure, Environmental Performance, and Firm Size on the Financial Performance of Coal Mining Subsector Firms - Devi Alita Solehsi; Titiek Rachmawati (Indonesian Journal Publisher, 2026)
This study looks at how the financial success of coal mining companies listed on the Indonesia Stock Exchange is affected by disclosure of carbon emissions, environmental performance, and company size. Using a quantitative approach with purposive sampling, six companies were selected as the sample. Carbon emission disclosure was measured using Carbon Emission Disclosure (CED), and environmental performance was assessed using environmental costs and PROPER ratings. Total company assets were used as a proxy variable, and financial performance was evaluated using ROA and ROE. SmartPLS 3 was used to analyze PLS-SEM data. The findings demonstrate that environmental management expenses lower short-term profitability and that disclosure of carbon emissions has a detrimental impact on both financial and environmental performance. Firm size has a positive, albeit slight, effect on financial performance. In conclusion, environmental sustainability efforts by coal mining companies help maintain corporate legitimacy and relationships with stakeholders, but they do not directly improve financial performance.